Producers’ quality policies and retailers’ pricing: Honey a case study - SILLANI, SANDRO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2006)
Distributors’ strategies and marketing activities influence always more those of the producers. In this setting whether the product quality policies of honey producers find a verification in the retailers’ pricing or not has been considered. A complex situation has emerged: 1) retail pricing in discounts considers the product quality policies of collective producers and particularly of the Italian origin certification 2) in super- and hypermarkets retail pricing considers mainly brand policies of producers 3) in herbalists’ shops, retail pricing does not consider the product quality policies of producers but only the price image of the trade point.